IDENTIFIKASI PERMUKIMAN KUMUH DI KELURAHAN TALUMOLO KECAMATAN DUMBO RAYA KOTA GORONTALO (Identification of Slum Settlement in Kelurahan Talumolo Kecamatan Dumbo Raya Kota Gorontalo) - Muhammad Rijal Syukri; Sri Sutarni Arifin (Universitas Muhammadiyah Gorontalo, 2018)
Abstract - The high number of urban residents due to a large number of migrants caused the reduction of land for settlements. This triggered the emergence of slums in various areas of the city. Dumbo Raya sub-district is a coastal area that is geographically flanked by the sea and hills. This condition causes the region to be very vulnerable to the disaster so that the growth of irregular or well-structured settlements will increase the chances of a disaster occurring. This study aims to determine the slums in Talumolo Subdistrict, Dumbo Raya District based on several indicators that have been determined and obtain data in the form of the area of slum identified. This study also aims to determine the level of a slum in the selected area. The method used in this research is through the application of Geographic Information System (GIS) and data analysis of questionnaires through mathematical calculations. Through this study obtained results in the form of: 1) Determination of locations included in the slum area based on 6 (six) variables namely non-economic vitality, economic vitality, land status, condition of infrastructure facilities, commitment of local governments and priority handling; 2) The results of identification and delineation of slum areas in Talumolo Village indicate that there is a slum area of 32,235 hectares with MEDIUM classification. Keywords: region, settlement, slum, Gorontalo, urban Abstrak – Tingginya jumlah penduduk kota akibat banyaknya pendatang menyebabkan berkurangnya lahan untuk permukiman. Hal ini memicu munculnya permukiman kumuh pada berbagai wilayah kota. Kecamatan Dumbo Raya merupakan wilayah pesisir yang secara geografis wilayahnya diapit oleh laut dan perbukitan. Kondisi ini mengakibatkan wilayah ini sangat rawan dengan bencana sehingga pertumbuhan permukiman yang tidak teratur atau tertata dengan baik akan memperbesar peluang terjadinya bencana. Penelitian ini bertujuan untuk menentukan kawasan kumuh yang ada di Kelurahan Talumolo Kecamatan Dumbo Raya berdasarkan beberapa indikator yang telah ditetapkan dan memperoleh data berupa luas kawasan kumuh yang diidentifikasi. Penelitian ini juga bertujuan untuk menentukan tingkat kekumuhannya kawasan yang terpilih. Metode yang digunakan pada penelitian ini adalah melalui aplikasi Sistem Informasi Geografis (SIG) dan analisis data hasil kuisioner melalui hitungan matematis. Melalui penelitian ini diperoleh hasil berupa : 1) Penentuan lokasi yang termasuk ke dalam kawasan kumuh disusun berdasarkan 6 (enam) variabel yaitu vitalitas non ekonomi, vitalitas ekonomi, status tanah, kondisi prasarana sarana, komitmen pemerintah daerah dan prioritas penanganan; 2) Hasil identifikasi dan deliniasi kawasan permukiman kumuh di Kelurahan Talumolo menunjukkan bahwa terdapat kawasan kumuh seluas 32,235 hektar dengan tingkat kekumuhan SEDANG. Kata kunci: kawasan, permukiman, kumuh, Gorontalo, perkotaan